O espaço nos contos de Antonio Carlos Viana: do texto escrito ao vídeo criativo por estudantes do 9º ano do ensino fundamental - Reis, Sarah Regina Santos dos (2021)
Commonly, it is the school's mission to highlight the essentiality of reading and literature for human beings and the transformative power they have.We support this view mainly in Antonio Candido (2004), who defends that literature is a right that any and every individual should have access to. Although contemporaneity favors contact with more imagetic and informative texts, by labeling literary as complex and difficult to interpret, it is understood that elementary school teachers, especially, should not deny this right to the student, but rather intensify the accessibility to that asset. Furthermore, in effective teaching, even though the short story is a widespread textual genre in the basic education curriculum, it is noticed that many students experience difficulties in reading and interpreting it, as well as in identifying aspects of the genre, such as building elements of space/environment and its implication in the formation of the individual's identity. The present research project was carried out with the only 9th grade class at the Colégio Estadual Monsenhor Olímpio Campos, in the municipality of Itabaianinha/SE, with the main purpose of promoting an experience with the literary art of the contemporary Sergipe writer Antonio Carlos Viana, emphasizing the element narrative of the fictional space/environment in the short stories “Santana Quemo-Quemo”, “Quando meu pai voltou” and “Dia de parir cabrito”, from the book Cine Privê (2009), in order to foment the formation of readers capable of understanding the senses of the texts and produce others in a meaningful and critical way.The proposal application of a didactic sequence based on and adapted under the model of Rildo Cosson (2009) predicted the elaboration/execution of a pedagogical notebook and the production of minute videos, which facilitate the achievement of the objectives intended in this research and result in a product replicable by other professionals. Thus, the aim was to provide students with the opportunity to develop an appropriate literary literacy, mainly by highlighting the magnitude of the work of local artists such as Antonio Carlos Viana, and with pedagogical activities that value the artistic-literary field. As a theoretical framework, arguments regarding literary literacy, reader education and literature in general predominated (BOSI, 2015; CANDIDO, 2004, 2006 and 2012; COSSON 2009; FERNANDES, 2011; FREIRE, 2011; SOARES, 2011, STREET, 2014); and the short story, space and chosen author (ALMEIDA, 2014; BACHELARD, 2008; DIMAS, 1987; FILHO, 2019; GANCHO, 2009; GOTLIB, 2006).